“When You Feel Like There is No Trust in the Profession”—Midwives and Obstetricians Facing Complicated Cases - Jägervi, Lotta; Svensson, Kerstin (Professions and professionalism, 2025)
This study examines how two collaborating professions, midwifery and obstetrics, are influenced by women requesting caesarean sections. The empirical material consists of semi-structured interviews with Swedish midwives (n=6) and obstetricians (n=6). Analysed through Tilly’s terms, the categorical pair and triad, midwife and obstetrician function as complementary categories in a triad with the women they encounter. Midwifery is a profession with connotations of closeness, understanding, and a unique connection to birth. It is challenged when women reject support or the idea of vaginal birth as empowering. Obstetrics, as a profession, relates to medical expertise, distance, and overview. It is challenged when their knowledge and authority are rejected. Both professions rely on each other’s complementary roles for support. The midwife draws on the obstetrician’s authority, while the obstetrician draws on the midwife’s empathic knowledge of the woman. When strongly challenged, they uphold their defined positions by questioning the woman’s judgement and rationality.